2014
DOI: 10.1007/s11250-014-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of peste des petits ruminants virus in formalin-fixed tissues

Abstract: Peste des petits ruminants virus that causes a highly infectious and often fatal disease of sheep and goats is confirmed by various diagnostic techniques among them being isolation of the virus from cell culture systems, viral ribonucleic acid (RNA) detection by molecular assays, and viral antigen detection by immunocapture enzyme-linked immunosorbent assay (IC ELISA), immunohistochemistry (IHC), and AGAR gel test. Whereas most of the confirmatory diagnostic procedures require pathological samples to be stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It was confirmed that the herd was infected with PPRV when the outbreak occurred. In the study, it should be noted that PPRV were detected from the formalin-fixed tissues samples which have several advantages: to prevent the spread of the virus, do not need cold chain transport and archived pathological tissues samples can be used for retrospective study, without affecting detection of PPRV (Kihu et al 2015). Phylogenetic analysis showed that all involved Chinese strains in the study belonged to lineage Ⅳ, but in different sub-branches with Tibetan strains of 2007(Bao, et al, 2014, Wu et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that the herd was infected with PPRV when the outbreak occurred. In the study, it should be noted that PPRV were detected from the formalin-fixed tissues samples which have several advantages: to prevent the spread of the virus, do not need cold chain transport and archived pathological tissues samples can be used for retrospective study, without affecting detection of PPRV (Kihu et al 2015). Phylogenetic analysis showed that all involved Chinese strains in the study belonged to lineage Ⅳ, but in different sub-branches with Tibetan strains of 2007(Bao, et al, 2014, Wu et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…To detect canine distemper virus RNA in FFPE tissues, Liang et al (2012) used in situ hybridization (ISH) whereas Seimon et al (2013) used RT-PCR and ISH. Furthermore, detection of PPRV specific RNA in FFPE tissues by real time RT-PCR has been reported (Kihu et al, 2015). Detection of PPRV RNA in FFPE samples allow to use FFPE tissues in the confirmation of PPR in laboratories where fresh tissues are not available for extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Effective disinfectant agents include alcohol, ether, phenol, sodium hydroxide and common detergents. In areas where PPR is endemic, the commonly employed control mechanism is vaccination (Kihu et al, 2015). The virus can survive for long periods of time in chilled or frozen tissues.…”
Section: Preventation Control and Vaccinationmentioning
confidence: 99%
“…New animals should be quarantined for three weeks before allowing them to mix with the flock. In a case of PPR outbreak, animals with signs of PPR should be isolated immediately and sheep and goats around the outbreak area should be vaccinated as soon as possible (Blood et al, 1983;Diallo et al, 1995;Spickler and Roth, 2006;Kihu et al, 2015). Vaccination is the most effective way to gain control epidemic PPR.…”
Section: Preventation Control and Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation